A religiosidade na voz de Pena Branca e Xavantinho - Paula, Andréa Cristina de (2012)
This study examines the manifestation of religion in some songs written and/or sungs by Pena Branca and Xavantinho observing the relationship between the expression of the sacred and rustic poetry. The analysis of the corpus (7 songs that are part of the discography of two simple men of the interior of Brazil) reveals itself as an important tool for understanding human imagination, because, through poetry sung of these and other songs, these artists reflect the variety of faiths, cultures and histories that are part of Brazilian popular tradition. At the sound of a guitar and singing and simple way of living, Pena Branca and Xavantinho insert the flavor of the earth to PBM (Popular Brazilian Music), playing compositions by renowned artists in the world of Brazilian music, such as Milton Nascimento and Chico Buarque, authors of the Cio da Terra , a song considered a watershed in the career of the brothers, it was through it that the duo expands their audience and get national visibility. Pena Branca and Xavantinho also stands in the Brazilian music scene by promoting the rescue of country music roots in the dictatorship of the modern country music, keeping its main features, such as using the traditional viola, the conservation issues that relate to the rustic culture and how to sing as a duet. One of the inseparable elements of the rural context is certainly the religiosity, a theme that is constant in the repertoire of these artists. Studying the life stories of the brothers, it turns out that this recurrence has close relationship with the religious ideology that has both characterized by a religious syncretism, in which different faiths dialogue in harmony. To perform the analysis, were used as theoretical reference, imaginary scholars such as Gilbert Durand, Carl Jung, Bachelard, Cassirer, and researchers from Brazilian popular religiosity, as Carlos Brandão and Talles de Azevedo. This work followed the following steps: reading of the biography of Pena Branca and Xavantinho and studies about the history of country music, seeking to highlight the role played by the duo in the musical universe backcountry; study the aspects that permeate religion, noting its presence in songs in country music in general and, listening CDs recorded by the brothers and Pena Branca, in solo career; selection of songs that at first glance, showed the presence of the religious theme, analysis of the selected corpus. The survey results are organized into three chapters, in which one seeks to demonstrate the relevance of studying popular artistic production, of these two artists of Uberlândia, because getting to know the literary work of people that is closer to its reality. Through the voice of two afro descendents from the countryside who learn a little bit of imagery that covers much of the Brazilian population. The work on the religious voice of Pena Branca and Xavantinho demonstrates, therefore, how the sacred still survives in the imagination of men, may prove in many ways, even through the rhythmic rustic word.